A rare Wohlfahrtiimonas strain linked to human infection - Huang, Peiying; Yang, Chao; Lin, Meifang; Song, Guanghui; Qu, Ping-Hua; Chen, Li (Frontiers in Cellular and Infection Microbiology, 2025)
Wohlfahrtiimonas is an infrequently encountered Gram-negative bacterium capable of infecting humans and, in severe instances, precipitating sepsis. Presently, three species within the Wohlfahrtiimonas genus have been identified, with Wohlfahrtiimonas chitiniclastica being the sole species implicated in human infections. To date, there has been only one documented case of human infection with W. chitiniclastica in China. In this study, we present an additional case of human infection with a Wohlfahrtiimonas species. Notably, through 16S rRNA gene sequencing and whole-genome sequencing, the strain was identified as an unclassified species closely related to W. chitiniclastica DSM 18708T.